2011
DOI: 10.1021/nn2025836
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanobranched Indium–Tin-Oxide Anode for Organic Solar Cells

Abstract: A nanostructured three-dimensional (3D) electrode using transparent conducting oxide (TCO) is an effective approach for increasing the efficiency of optoelectronic devices used in daily life. Tin-doped indium oxide (ITO) is a representative TCO with high conductivity and a high work function for anode applications. This paper reports the fabrication of a large-area ITO nanostructure with a branch shape using an electron beam evaporation process at temperatures as low as 80 °C, which was free of any carrier gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 35 publications
1
75
0
2
Order By: Relevance
“…[http://dx.doi.org/10.1063/1.4875457] Indium tin oxide (ITO) or Sn doped In 2 O 3 nanowires (NWs) are important as transparent conducting oxides (TCOs) for the fabrication of solar cells, [1][2][3] flexible displays, 4 and ultra violet light emitting diodes [5][6][7][8][9] because it has been suggested that higher Sn doping levels and conductivities can be attained in ITO NWs compared to bulk ITO. So far ITO NWs have been grown by carbothermal reduction of In 2 O 3 and SnO 2 5 but the control of stoichiometry is not trivial as it has been observed that SnO 2 NWs may be obtained even when a higher content of In 2 O 3 is used during carbothermal reduction carried out under an inert gas flow at elevated temperatures 10,11 which also leads to the non-intentional incorporation of carbon.…”
Section: Fermi Level Position © 2014 Author(s) All Article Contentmentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4875457] Indium tin oxide (ITO) or Sn doped In 2 O 3 nanowires (NWs) are important as transparent conducting oxides (TCOs) for the fabrication of solar cells, [1][2][3] flexible displays, 4 and ultra violet light emitting diodes [5][6][7][8][9] because it has been suggested that higher Sn doping levels and conductivities can be attained in ITO NWs compared to bulk ITO. So far ITO NWs have been grown by carbothermal reduction of In 2 O 3 and SnO 2 5 but the control of stoichiometry is not trivial as it has been observed that SnO 2 NWs may be obtained even when a higher content of In 2 O 3 is used during carbothermal reduction carried out under an inert gas flow at elevated temperatures 10,11 which also leads to the non-intentional incorporation of carbon.…”
Section: Fermi Level Position © 2014 Author(s) All Article Contentmentioning
confidence: 99%
“…15,16 Thus, significant research has been directed toward finding a suitable replacement for ITO. Nanostructured conducting materials such as Ag nanowires, 17,18 graphenes, 19 poly (3, 4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS), 20 metal grids, [21][22][23][24][25] ITO nanobranch, 26,27 and ZnO-doped In 2 O 3 28 have been evaluated as flexible electrodes to overcome the shortcomings of ITO. Metal nanowires show high transmittance (∼86%) and relatively low sheet resistance (∼16 Ω∕□), but poor thermal stability and rough surface morphology causing poor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Graphene, PEDOT:PSS, and ITO nanobranch have superior flexibility, but are limited by low conductivity and lack of uniformity in large areas. 20,26,31 Metal grids have also been used for transparent electrodes, with excellent conductivity and flexibility. However, fabrication procedures are high cost and complex.…”
Section: Introductionmentioning
confidence: 99%
“…Although several groups have fabricated In 2 O 3 -based networks made up of diverse onedimensional (1D) structures, such as nanoribbons [10,11], nanofibers [12], nanowires [13,14], nanorods [15,16]. Based on these networks, several types of devices, including field effect transistor [17], flat-panel displayers [6], solar cells [18,19], and gas sensors [20] have been developed.…”
Section: Introductionmentioning
confidence: 99%